Método fenomenológico y su aplicación educativa - Santana Sánchez, Marcos Daniel (2015)
This article there outlined the possibility of knowing the manifestation of the educational reality from the methodological advocated phenomenology of Husserl and Hartmann. For the application and explanation it begins with the separation of the educational phenomenon. On the one hand it refers to the subjects and the other to the space known as curricular area and in this sequence, we can outline some strategies for the use of the phenomenological method in the classroom. The spotlight falls on the pretense of reaching an objective and critical analysis of the educational phenomenon and the proposed knowledge.